2000
DOI: 10.1002/1097-458x(200007)38:7<504::aid-mrc710>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

NMR studies of exchange between triazine rotamers

Abstract: Proton and 13C solution‐state spectra were obtained for a substituted triazine and assignments made for the signals using different solvents. Site‐exchange effects were observed in 1H spectra at different temperatures below ambient for a CD3OD solution. The bandshapes were fitted for three‐site exchange and the relevant rate constants extracted. The exchange was attributed to internal rotation of the substituents about the triazine ring. Activation parameters were calculated: for exchange between one pair of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…In solution, azo and hydrazone tautomers exist in an equilibrium depending on temperature, solvent and substitution pattern. The equilibrium in solution has been studied by UVvisible (Traven et al, 1980; and NMR spectroscopy (Chippendale et al, 1999;Lycka et al, 2000;Birkett et al, 2000;Machacek et al, 2000;Alarcon et al, 2004). Solid-state NMR investigations have also been carried out (Chippendale et al, 1981;Olivieri et al, 1989;McGeorge et al, 1996McGeorge et al, , 1998.…”
Section: Commentmentioning
confidence: 99%
“…In solution, azo and hydrazone tautomers exist in an equilibrium depending on temperature, solvent and substitution pattern. The equilibrium in solution has been studied by UVvisible (Traven et al, 1980; and NMR spectroscopy (Chippendale et al, 1999;Lycka et al, 2000;Birkett et al, 2000;Machacek et al, 2000;Alarcon et al, 2004). Solid-state NMR investigations have also been carried out (Chippendale et al, 1981;Olivieri et al, 1989;McGeorge et al, 1996McGeorge et al, , 1998.…”
Section: Commentmentioning
confidence: 99%
“…Coupling values in Table 6 are about as expected. Hydrogen decoupling of the 13 C spectrum showed that the 3.72 Hz triplet for the methylene of 20 results from long-range coupling to the methylene in the other ethyl group rather than to fluorine nuclei.…”
Section: Carbon-13mentioning
confidence: 99%
“…The geometric structure of 1,3,5-triazine was determined by Marchal and Canet by measurements of direct couplings from observation of 13 C and 15 N satellites in oriented molecules in nematic phase [9]. Several groups have considered the effects and rates of restricted rotation about the bond between a triazine ring carbon and an unsymmetrically substituted amino nitrogen attached to the carbon [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…11 For a number of amino 1,3,5 triazines, the activation energies have been determined and the rotation barriers have been calculated theoretically. [11][12][13][14][15] The researchers cited at tribute the hindered rotation in substituted amino 1,3,5 triazines to the electron withdrawing properties of the triazine ring, resulting in a higher C tr -N am bond order (tr is triazine, am is amine). Earlier studies into the dy namic effects are represented by scattered examples.…”
mentioning
confidence: 99%
“…For some aminodichlorotriazine derivatives, the problem of solubility at low temperatures proved unsolvable. 11,12,15 Owing to the presence of fluorine in perfluoroalkoxy 1,3,5 triazine molecules, dynamic experiments can take advantage of 19 F NMR spectroscopy, which requires less experimental time than 13 C NMR and covers a broader range of chemical shifts than 1 H NMR, which is signifi cant for shortening the experimental time.…”
mentioning
confidence: 99%